Meta Analysis the Association between Social Support and Quality of Life of People Living with HIV/AIDS - Maria Regina Tri Yonita; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Social support is a form of interpersonal relationship where the social environment provides assistance in the form of emotional attention, instrumental assistance, providing information, appreciation or assess